Effect of radial shock wave therapy on pain and muscle hypertonia: a double-blind study in patients with multiple sclerosis. (April 2015) - Marinelli, L; Mori, L; Solaro, C; Uccelli, A; Pelosin, E; Currà, A; Molfetta, L; Abbruzzese, G; Trompetto, C
Background: Radial shock wave therapy (RSWT) has been extensively used in rehabilitative medicine to treat pain, and more recently muscle hypertonia, in patients with cerebral palsy and stroke. Objectives: To assess the long-term effects of RSWT in a cohort of subjects affected by multiple sclerosis (MS) who were suffering from painful hypertonia of ankle extensor muscles. Methods: In this randomised, double blind, placebo-controlled study, we treated 34 patients with four sessions of RSWT (once weekly) and treated 34 patients with placebo. Participants were assessed at baseline, 1 week after the first session, and 1 week and 4 weeks after the last session. We measured pain using the visual analogue scale for pain, while we assessed muscle tone using the modified Ashworth scale and evaluated spinal excitability using the H-reflex. Results: After RSWT, muscle tone decreased 1 week after the last session and pain decreased at all the follow-up evaluations, while spinal excitability was unaffected. No significant changes were found after the placebo treatment. Conclusions: RSWT can reduce pain and muscle tone in MS patients without adverse effects. The lack of RSWT effects on spinal excitability supports the idea that RSWT is likely to act on non-reflex hypertonia, for example reducing muscle fibrosis.